Evaluation of psychological stress in pregnant females during COVID era - Kaur, Prabhneet; Sehgal, Alka; Tandon, Rimpy; Deepti; Arun, Priti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anxiety and depression may affect 20-40% of pregnant women with concerns about foetal well-being, maternal health, social and financial support, and even death. During the COVID Era, fear of contracting illness, restricted availability of healthcare services, and stresses secondary to job loss were expected which led to an increase in pre-existing psychopathology as well as new onset of psychiatric disturbances. Hence it was decided to carry on a screening study to evaluate psychological stress among pregnant women during the COVID-19 pandemics related to it. Methods: A questionnaire-based prospective study was conducted amongst pregnant women visiting Government Medical College and Hospital, Chandigarh in three months (June 2020 to August 2020) during the COVID Era. Among 162 subjects, 30 pregnant healthcare workers and 32 COVID-positive pregnant women were included. All COVID-appropriate behaviour and precautions were followed while filling out the questionnaires. Results: Fear symptoms were present in 52.5% of pregnant women. All the fears were significantly more amongst the healthcare workers which could be due to more knowledge or since they were direct observers of COVID load. Fear of breastfeeding was more common among COVID-19 positives and was significant. Conclusions: Screening and education should be made necessary components of prenatal care with the implementation of a multidisciplinary approach to tackle this aspect of maternal mental health.